Transcranial direct current stimulation and repetitive transcranial magnetic stimulation in consultation-liaison psychiatry - Valiengo,L.C.L. (2013)
Patients with clinical diseases often present psychiatric conditions whose pharmacological treatment is hampered due to hazardous interactions with the clinical treatment and/or disease. This is particularly relevant for major depressive disorder, the most common psychiatric disorder in the general hospital. In this context, nonpharmacological interventions could be useful therapies; and, among those, noninvasive brain stimulation (NIBS) might be an interesting option. The main methods of NIBS are repetitive transcranial magnetic stimulation (rTMS), which was recently approved as a nonresearch treatment for some psychiatric conditions, and transcranial direct current stimulation (tDCS), a technique that is currently limited to research scenarios but has shown promising results. Therefore, our aim was to review the main medical conditions associated with high depression rates, the main obstacles for depression treatment, and whether these therapies could be a useful intervention for such conditions. We found that depression is an important and prevalent comorbidity in a variety of diseases such as epilepsy, stroke, Parkinson's disease, myocardial infarction, cancer, and in other conditions such as pregnancy and in patients without enteral access. We found that treatment of depression is often suboptimal within the above contexts and that rTMS and tDCS therapies have been insufficiently appraised. We discuss whether rTMS and tDCS could have a significant impact in treating depression that develops within a clinical context, considering its unique characteristics such as the absence of pharmacological interactions, the use of a nonenteral route, and as an augmentation therapy for antidepressants.